Prejudice towards African American Characters in 12 Years a Slave Film - Hidayah, Nur; Ariani, Setya; Sartika Dewi M, Jonathan Irene (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2023)
Prejudice is a thought or assumption that is not necessarily true of a person or group based on their membership background. There are some hostile actions in prejudice, namely: (1) Antilocution, (2) Avoidance, (3) Discrimination, (4) Physical Attack, and (5) Extermination. With Allport's theory of prejudice, the researcher analyzes a film called 12 Years a Slave. The film is analyzed more deeply to find subtitles and scene pieces that contain elements of hostile actions in prejudice. To get the elements of prejudice in the film, the writer uses character theory and characterization to find elements of prejudice that occur in the characters in the film.  This study used a qualitative method because it requires a deep understanding of a phenomenon that occurs.  In the results of this study, the researcher found that there are four types of acts of prejudice, namely: (1) Antilocution, (2) Discrimination, (3) Physical Attack, and (4) Extermination. The most frequently used act of prejudice in this film is a physical attack. Based on the research in this study, the physical attacks in the film occurred because of the lack of self-control of white people over African Americans. More deeply, another reason is because of the mode of justification for the violence that white people against African Americans through the Bible. Lastly, because of the legalization of the sale and purchase of slaves, there was a sense of ownership that allowed white people to do anything to their slaves.